Entrepreneurship in Costa Rica: stagnation in the transition to innovation - Chaves Núñez, Manuel (2015)
Costa Rica is stuck in a transition phase between an efficiency-based economy and an innovation-based economy and is not promoting the necessary entrepreneurial conditions that would lead to the required transformation.  Meanwhile, other countries in the region are in a better position to encourage entrepreneurship. In this situation, it is important to ask which are the conditions regarding entrepreneurship in Costa Rica that could improve the transition to an innovation-based economy.To improve this situation, the country must develop an inter-institutional support program that attracts direct foreign investment and linkages between businesses, improve human capital, provide training, incubation and funding, and have better articulation of public policy.